EVALUASI PENGENDALIAN PENJUALAN PRODUK PLASTIK UNTUK MENGURANGI KERUGIAN - Elizabeth Tiur Manurung; Paulina Permatasari; Arthur Purboyo; Levithia Rinas (JRAK, 2020)
Internal control review towards the revenue cycle is required to evaluate the effectiveness and efficiency of the existing management in order to support the achievement of company goals, and provide recommendations to allow corrective actions. These should be taken in order to review the role of internal control in increasing sale performance. This research used descriptive study method which could help to think systematically about various variables on a particular situation, to provide ideas for further research and to make simple decisions from the research that was done. Data collection techniques conducted were literature study and field study at Bandung Plastic company. Based on the result of internal control analysis, it was discovered that internal control set by the company will help company to handle loss of bad debt expenses, avoid fictitious sales, reduce improper sales target, reduce re-delivery cost, reduce erroneous task, and reduce environmental pollution.